Cutting the Gordian Knot: Identifiability of anaplerotic reactions in Corynebacterium glutamicum by means of 13C‐metabolic flux analysis. Issue 3 (18th October 2015) - Kappelmann, Jannick; Wiechert, Wolfgang; Noack, Stephan
ABSTRACT: Corynebacterium glutamicum is the major workhorse for the microbial production of several amino and organic acids. As long as these derive from tricarboxylic acid cycle intermediates, the activity of anaplerotic reactions is pivotal for a high biosynthetic yield. To determine single anaplerotic activities 13 C‐Metabolic Flux Analysis ( 13 C‐MFA) has been extensively used for C. glutamicum, however with different network topologies, inconsistent or poorly determined anaplerotic reaction rates. Therefore, in this study we set out to investigate whether a focused isotopomer model of the anaplerotic node can at all admit a unique solution for all fluxes. By analyzing different scenarios of active anaplerotic reactions, we show in full generality that for C. glutamicum only certain anaplerotic deletion mutants allow to uniquely determine the anaplerotic fluxes from 13 C‐isotopomer data. We stress that the result of this analysis for different assumptions on active enzymes is directly transferable to other compartment‐free organisms. Our results demonstrate that there exist biologically relevant metabolic network topologies for which the flux distribution cannot be inferred by classical 13 C‐MFA. Biotechnol. Bioeng. 2016;113: 661–674. © 2015 Wiley Periodicals, Inc. Abstract : A thorough and systematic study of the flux observability problem in 13 C‐MFA is presented and applied to the anaplerotic reactions of Corynebacterium glutamicum, a complex example of five simultaneously active reactions. It is shown that the full set of anaplerotic reactions cannot be inferred from stationary 13 C‐labeling data even if the 13 C‐enrichment in every carbon atom is known. Using a focused network model of the anaplerotic node identifiable combinations of fluxes and measurements are derived.